Interorganisational knowledge transfer: the role of the gatekeeper. (27th February 2007) - Cranefield, Jocelyn; Yoong, Pak
This paper reports on a research project that investigated the key factors impacting on interorganisational knowledge transfer during a collaborative project involving a group of New Zealand State Sector organisations. Interviews were undertaken with seven gatekeepers (boundary-spanning individuals). The gatekeepers were found to have performed multiple roles, playing a critical part in enabling knowledge transfer throughout the project. These roles were: (1) flag-bearer for their organisation, (2) project advocate within their organisation, (3) translator and interpreter of new knowledge, (4) scout (a seeker of knowledge), (5) facilitator of knowledge sharing and knowledge creation and towards the latter stages of the project, (6) storyteller and (7) in-house expert.